A study of realisation of requirement type modal meaning in the writings of selected Malay ESL students - Mohd Azlan Shah Sharifudin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
It has been concurred by many that modality is not an easy subject for ESL learners. The ability to manipulate the system of modality, however, is very crucial in the writing process of an argumentative essay. This study was conducted to examine 50 Kolej RISDA Melaka's students' understandings of the system as well as their performance in realising the modal meaning, particularly requirement modal meaning, within argumentative context. The results from the analysis of the students' compositions revealed that their understanding and performance of this subject was still inadequate in a way that the distributions of modal operators and modal meanings found in their writings were disproportionately concentrated to modal operators will, can and should, and modal meaning likelihood (positive), requirement (positive), ability (positive), and potential (positive). Other than the ones mentioned were scarcely used. It was also discovered that the percentage of their accuracy in realising all modal meanings, especially requirement modal meaning, was rather high. Notwithstanding, the high percentage is believed to have been contributed by other reasons than their understandings. Plausible explanations for each finding were given. That aside, students were also detected to have employed avoidance strategy in their writings, negative transfers from their native language were spotted, modal operators chosen to be formally taught to students in secondary schools were inadequate, and lastly, inaccuracies in formal structures of clauses employing modal operators were also identified although the frequencies are minimal.